STATISTICAL ANALYSIS OF RESULTS STAND EXPERIMENTAL RESEARCHES OF CHANGE OF AXIAL LOADING ON CHISELS OF DIFFERENT TYPES - Мойсишин, Василь Михайлович; Витязь, Олег Юлійович; Фем’як, Ярослав Михайлович; Масьовський, Андрій Ігорович; Жовнірук, Роман Андрійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
As a result of stand experimental researches of change of the axial loading on well of mining hole at the boring drilling by chisels different types are set, that the instantaneous values of the axial loading answer the normal law of distributing, and the explored casual process is stationary and ergodic. It enables during the analysis of underlying structure of axial dynamic force which is the constituent of the general axial loading, to use only one realization of record of change of axial effort on well of mining hole.